Does A Child Quantity-Quality Trade-Off Exist? Evidence from the One-Child Policy in China - Yue Huang (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Evidence on the existence of a trade-off between child quantity and child quality, as suggested by Gary S. Becker, is still inconclusive. This also holds true for empirical studies on China that exploit for identification the country s One-Child Policy (OCP) as an exogenous source of variation in the number of offspring. However, this body of literature suffers from a number of shortcomings, in particular measurement error in the key policy variable (a household s coverage by OCP) and in the outcome variable of interest (schooling choices, i.e. child quality). Using census data for China and a continuous OCP variable that can address these shortcomings, the results provide evidence for the existence of a sizeable quantity-quality trade-off within households with mothers who are Han and have agricultural Hukou.
Keywords: J13; J18; I20; 330